Dampak Perceraian Orang Tua terhadap Kesejahteraan Anak - Siti Zaenab Muta'aliyah; Siska Nur Cahyani; Sri Marwani; Shabrina Yumna Nur Aziizah; Dian Novita Siswanti; Eka Sufartianinsih Jafar (CV. ITTC INDONESIA, 2026)
Divorce is a growing social phenomenon that affects not only couples but also children’s well-being. Children who experience parental divorce tend to face various challenges, including psychological, emotional, social, and academic difficulties. This study aims to examine the impact of parental divorce on children’s well-being. The method used is a literature review by analyzing relevant journals and scientific articles published within the last five years. The findings show that parental divorce tends to cause negative impacts, such as sadness, anxiety, depression, feelings of loss, decreased self-confidence, and difficulties in social relationships and academic performance. However, in some situations, divorce may also bring positive outcomes, such as increased independence, maturity, and the ability to cope with problems. Children’s well-being after divorce is influenced by several factors, including social support, the quality of parent-child relationships, coping skills, and forgiveness. Therefore, parental divorce has complex effects on children’s well-being, and emotional support, psychological intervention, and a supportive social environment are needed to help children adapt effectively.